Investigating Communities of Practice (CoPs) and Transient International Groups (TIGs) in BELF Contexts - Marie-Luise Pitzl (Iperstoria, 2019)
Being relevant to the study of ELF more generally, the notion of Community of Practice (CoP) has been especially central to the work of some BELF scholars (e.g. Ehrenreich 2009, 2018; Cogo 2016). While many institutional business contexts in which ELF is used regularly (alongside and mixed with other languages) fit the criteria of a CoP, other (B)ELF contexts do not. Furthermore, even many existing CoPs tend to be comprised of smaller (and often more fleeting) groups and multilingual teams. To describe these smaller and less stable inter-/transcultural social clusters, recent work on ELF has proposed the notion of Transient International Groups (TIGs) (Pitzl 2018). This article will engage with characteristics of CoPs and TIGs in order to show how these two concepts complement each other with regard to BELF research. Discussing central criteria of the CoP framework and subsequently introducing key propositions of the TIGs approach, in particular concerning metadata and data analysis, the article highlights the research potential of exploring TIGs alongside more established CoPs. It is argued that working with both concepts and approaches – CoPs and TIGs – is likely to help us gain a more sophisticated understanding of the organizational and social dynamics that influence BELF communication.